PENGARUH PENGAWASAN INTERNAL, KEMAMPUAN TEKNIK PERSONAL, PROGRAM PENDIDIKAN DAN PELATIHAN TERHADAP KINERJA SISTEM INFORMASI AKUNTANSI (Studi Kasus Pada kantor Kementerian Agama Kab/Kota di Propinsi Banten) - Unayah, Enah (Pascasarjana Universitas Sultan Ageng Tirtayas, 2020)
This study aims to examine the influence of internal control, personal technical skills, education programs and training on the performance of accounting information systems. The population in this study is the sub-section of administration in the Office of the Ministry of Religious Affairs in the Regency / City in Banten province with the research sample is the Head of Sub division of administration and application operator employees. The sampling method used is purposive sampling. The data in this study was obtained by distributing questionnaires directly to the respondents. Data in this research is analyzed by strcutural equation modeling (SEM) method, with Partial Least Square (PLS) approach. The results of this study indicate that internal control has a significant positive effect on the performance of accounting information systems, the ability of personal techniques has no significant effect on the performance of accounting information systems. While education and training programs have a significant positive effect on the performance of accounting information system.